Smartphone Addiction, Sleep Quality, and Temporomandibular Disorders Among Dental Students: A Cross-Sectional Analysis - Taşkaldıran, Ezgi Sıla; Varlıhan, Gülce Nil; Naghizadeh Asgari, Sevda (The European Research Journal, 2026)
Objectives: The rapid digitalization of daily life has made smartphone dependence a growing public health concern, particularly among university students. This study explored how smartphone addiction relates to sleep quality, temporomandibular disorder (TMD), and bruxism in dental students at different stages of training. Methods: A total of 259 participants completed validated questionnaires assessing the Smartphone Addiction Scale–Short Version (SAS-SV), Pittsburgh Sleep Quality Index, bruxism, and TMD symptoms. Results: Nearly half of the students exhibited signs of smartphone addiction. Higher addiction scores were significantly correlated with poorer sleep quality and greater TMD severity, particularly among preclinical and doctoral students, while no significant relationship was found between bruxism and addiction scores. Conclusions: These results imply that excessive smartphone use may silently impact mental and orofacial health by causing stress, sleep disturbances, and postural strain. Promoting healthier technology habits and addressing digital dependence could be key to protecting the well-being of future dental professionals.